Hazard-free treatment and resource utilisation of electrolytic manganese residue: A review. (15th July 2021) - He, Shichao; Jiang, Daoyan; Hong, Minghao; Liu, Zhihong
Abstract: China has the largest output of electrolytic manganese metal (EMM), accounting for more than 98% of the world's total annual production. Meanwhile, it has also caused serious environmental pollution and damage, among which the main pollutant is electrolytic manganese residue (EMR). EMR contains a large amount of NH4 + -N, Mn, Mg, and other elements such as soluble sulphate, SeO2, and heavy metal elements. The unmanaged stockpiled EMR generally exposed to open air not only causes serious pollution in the surrounding surface water, groundwater, soil, air, and ecosystems, but also poses a serious threat to the health and survival of the residents in the surrounding area. For the EMM industry to support development and human society, the treatment and disposal of EMR must become more sustainable. This review provides a detail on the origin, main phase compositions, hazardous components of EMR, and status quo of hazard-free treatment and resource utilisation of EMR in the last 30 years. In particular, this study systematically summarizes applicability of different type of technologies to hazard-freely treat and utilize EMR, including valuable elements recovery, stabilisation/solidification and electrokinetic remediation, building materials, wastewater treatment materials, soil amendments, and other functional materials. In addition, the advantages and disadvantages of these technologies have also been scientifically evaluated. At the end of the review, existing challenges as well as future prospects of hazard-free treatment and resource utilisation of EMR are also discussed. Graphical abstract: Image 1 Highlights: The origin, main phase compositions, and hazardous components of EMR are introduced in detail. The pollution and damage caused by EMR are introduced in detail. The status quo of hazard-free treatment and resource utilisation of EMR are systematically reviewed. The challenges and prospects of hazard-free treatment and resource utilisation of EMR are proposed.